PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN OBSERVASI SISWA KELAS VII SMP NEGERI 22 PADANG - Melisa, Elda; Rasyid, Yulianti (Universitas Negeri Padang, 2019)
ABSTRACTthe purpose of this research are three, there are describes (1) skill of writing observation report text class VII SMP Negeri 22 Padang before using discovery learning model, (2) skill of writing observation report text class VII SMP Negeri 22 Padang after using discovery learning model, (3) the influence discovery learning model towards skill of writing observation report text class VII SMP Negeri 22 Padang. There are two research data, there are score of skill on writing observation report text class VII SMP Negeri 22 Padang before and after using discovery learning model. Based on the results of the study, it was concluded three things, there are (1) skill of writing observation report text class VII SMP Negeri 22 Padang before using discovery learning model qualifications are on enough with the average value of 69,97, (2) skill of writing observation report text class VII SMP Negeri Padang 22 after using discovery learning model with good qualifications are on average value of 81,90, and (3) the influence discovery learning model impact skill of writing observation report text class VII SMP Negeri 22 Padang degrees of significance 0,95 and dk = n-1 because thitung > ttabel (5,81 > 1,70).Kata kunci: Pengaruh, Model Discovery Learning, Teks Laporan Observasi